The impacts of expertise, conflict, and scientific literacy on trust and belief in scientific disagreements - Natasha van Antwerpen; Estelle B. Green; Daniel Sturman; Rachel A. Searston (Scientific Reports)
Abstract Media portrayals of scientific disagreements can blur distinctions between experts and non-experts, or include disagreements from vested individuals, potentially undermining trust in science and belief in scientific claims. We investigated how disagreeing sources’ expertise and conflicting interests impact trust in scientific experts and belief in their claims, and whether scientific literacy moderates these effects. Across three, 2 × 2 factorial experiments with a student (N = 105) online (N = 110), and general Australian sample (N = 105), participants read articles describing a scientific claim followed by a disagreeing source whose subject-matter expertise (present/absent) and vested interest (present/absent) were manipulated. Participants in all samples judged the original scientific expert as more trustworthy and their claims more believable when the disagreeing source lacked relevant subject-matter expertise. Among student participants, conflicts of interest also impacted belief in scientific claims (but not trust in the scientist), and scientific literacy enhanced sensitivity to expertise and conflict, however, the other samples were largely insensitive to vested interests, and scientific literacy had varied effects in these samples. Our results show disagreement in the news, even from questionable sources, can sway evaluations of scientific claims and scientists, and highlight the value of literacy-based interventions in science communication.